AUDIENCE'S PERCEPTION OF CULTURAL/ETHNIC STEREOTYPES IN TV SHOWS - Torres, Inés Galiano (European Scientific Journal, ESJ, 2015)
Ethnic Stereotypes in media and why they matter: Much research has focused on the existence of both positive and negative stereotypes in television. The fact is that stereotypes are still present in the media and have several implications for the ethnic and social groups included. Racial or ethnic stereotypes, which are the main topic in this research, are generalizations about an out-group. Processes of this research: This study examines relevant research articles about the portrayals in television of ethnic and cultural groups. Literature suggests that television still plays an important role in reinforcing stereotypes. These articles provide the starting point for future research about the possible effects on the audience regarding cultural stereotypes in TV shows, especially African American stereotypes; Latino stereotypes; Asian stereotypes; and interracial relationships. Results: The repeated depiction of cultural stereotypes in television shows reinforces and validates the notion of the ―other.‖ The articles reviewed for this research provide the most relevant findings regarding this issue. However, further research needs to be done to determine the possible effects on the audience and changes in attitudes towards different cultural or ethnic groups after the exposure to these stereotypes and how the effects could impact reallife interactions among different groups.